2018
DOI: 10.5194/asr-15-51-2018
|View full text |Cite
|
Sign up to set email alerts
|

An approach for the estimation of the aggregated photovoltaic power generated in several European countries from meteorological data

Abstract: Abstract. Classical approaches to the calculation of the photovoltaic (PV) power generated in a region from meteorological data require the knowledge of the detailed characteristics of the plants, which are most often not publicly available. An approach is proposed with the objective to obtain the best possible assessment of power generated in any region without having to collect detailed information on PV plants. The proposed approach is based on a model of PV plant coupled with a statistical distribution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…This statistical approach has also been employed in the Copernicus Climate Change Service to generate regional PV power for each region in Europe using the ERA5 reanalysis data set. As described by Saint-Drenan et al (2018), the parameters of the statistical regional model have been derived from the optimal tilt angle, allowing this model to be implemented anywhere in Europe without the need for a training data set. A comparison of the model output with the European Network of TSOs for Electricity data showed that this approach is well accepted.…”
Section: Regional Model Based On Statistical Analysis Of the Fleet Of Pv Systemsmentioning
confidence: 99%
“…This statistical approach has also been employed in the Copernicus Climate Change Service to generate regional PV power for each region in Europe using the ERA5 reanalysis data set. As described by Saint-Drenan et al (2018), the parameters of the statistical regional model have been derived from the optimal tilt angle, allowing this model to be implemented anywhere in Europe without the need for a training data set. A comparison of the model output with the European Network of TSOs for Electricity data showed that this approach is well accepted.…”
Section: Regional Model Based On Statistical Analysis Of the Fleet Of Pv Systemsmentioning
confidence: 99%
“…As a proxy for the observed levels of wind and solar PV electricity generation, we use the national-scale energy data sets developed in ECEM (Dubus et al 2017a,b;Saint-Drenan et al 2018; see also Troccoli et al 2018). While this is based on actual, observed generation data from across Europe, it is in fact modelled.…”
Section: Observation-based Datamentioning
confidence: 99%
“…Another work of them modifies this model into an unsupervised method that uses fuzzy arithmetic to model uncertainties and the aggregation effect [12]. Saint-Drenan et al construct the statistical distribution of PV configurations and estimate the region's PV generation by sampling PV plants from the statistical distribution [13]. These studies are essentially amplifying the power measurements of visible sites by the ratio of the region's total PV capacity to their capacity.…”
Section: Introductionmentioning
confidence: 99%